Design and implementation of a web platform for student tracking and notification using SMS and e-mail - Oviedo, Yuly Jazmin; Espítia, Karen Lorena; Pedraza, Luis Fernando (Visión electrónica, 2014)
This paper presents the design and implementation of a web platform for student tracking and notification using SMS and email (at a school called Instituto San Francisco (Bogotá,Colombia). Firstly, the document addresses the needs of the school, which represent the main concern for this academic web platform. Subsequently, this paper shows the analysis of technologies and describes the design of the platform based on the requirements of the institution. Additionally, the web platform performance analysis and testing results are included. Finally, results of implementing the academic web platform at Instituto San Francisco are provided together with the conclusions and recommendations drawn at the end of the project.